Web-Based Information System for Covid19 in Yemen - Abdulrahman Sharaf Mohammed Fadhel,; Ghazali, Rozaida (Applied Information Technology And Computer Science, 2021)
The world pandemic coronavirus (COVID19) has affected the Yemen health system and human healthcare is because of the high impacts of the lack of response to COVID19. Moreover, Yemen has been a disaster by concomitant outbreaks of other communicable diseases such as cholera, malaria and dengue the expense of primary healthcare support to the pandemic coronavirus will undermine existing health system strengthening efforts worsen the humanitarian crisis and will accentuate the impact of COVID19.  To develop a web-based information system to manage the coronavirus spreading impacts status and health system situation to enhance the health system's preparedness to facing the pandemic COVID19. This system will enhance the medical staff in Yemen for managing the COVID19 impacts through the methodology of developing a web-based information system for manage COVID19 status in Yemen. This system will help the medical staff monitor the states of coronavirus in each region. Developing an estimation module assists to estimate how COVID19 affect population and common chronic disease and the lack healthcare facility collapse and provide statistical results related to the COVID19 impacts.This will help the medical staff 11create strategies and health plans help on how to deal with and control with spreading impacts of COVID19 and provide the essential public health services needed. To update the public citizen of Yemen about the states of COVID19 spreads and awareness to the various information related to COVID19 impacts. The availability of assistive technology allows health officials to prepare and decide medical needs to confront the spread of viruses and to determine the danger of their spread and provide general needs to protect human healthcare.